2019
DOI: 10.1590/1413-81232018244.33802016
|View full text |Cite
|
Sign up to set email alerts
|

Dor, ansiedade e qualidade de vida relacionada à saúde bucal de pacientes atendidos no serviço de urgência odontológica

Abstract: Resumo O objetivo deste estudo foi avaliar associação entre dor pré-operatória, ansiedade e impacto da condição bucal na qualidade de vida dos pacientes atendidos no serviço de Urgência Odontológica da Universidade Federal dos Vales do Jequitinhonha e Mucuri. Estudo transversal retrospectivo foi conduzido avaliando dados clínicos de 240 prontuários de pacientes com idades entre 18 e 65 anos. A dor foi mensurada pela Heft-Parker Visual Analogue Scale; ansiedade, pela Corah’s Detal Anxiety Scale e qualidade de v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 41 publications
1
12
0
13
Order By: Relevance
“…These findings are in line with a study that evaluated institutionalized elderly people to determine the validity and reliability indexes of the dental screening instrument. This instrument is in good agreement with this indicator, even considering unstable pain and considering that it also depends on the elderly's episodic response (18,27) .…”
Section: Inter-examiner Agreement In the Application Of An Oral Health Assessment Instrument In Hospitalized Elderlymentioning
confidence: 66%
“…These findings are in line with a study that evaluated institutionalized elderly people to determine the validity and reliability indexes of the dental screening instrument. This instrument is in good agreement with this indicator, even considering unstable pain and considering that it also depends on the elderly's episodic response (18,27) .…”
Section: Inter-examiner Agreement In the Application Of An Oral Health Assessment Instrument In Hospitalized Elderlymentioning
confidence: 66%
“…Although these data may be greater than that actually found, once the scales used for this data collection does not evaluate the patient's reaction to a treatment session, but rather the predisposition to be anxious in a hypothetical answer, this is a number considered high. Thus, fear, anxiety and phobia, have been appointed as responsible for the extensive index of oral diseases and systemic manifestations, becoming a public health problem 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the surgeon-dentist, aware of the emotional Manifestation of Anxiety during Dental Treatment: Integrative Literature Review signifi cance must understand that the hostility shown by the patient refers to a situation which is developed during the dental treatment and that can aff ect his or her life quality 7 . Therefore, in spite of the great challenge, the professional must have a prior knowledge of the patient, his oer her family and the specifi c data of the region in which the patient lives, so that the surgeon dentist can understand it as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these results also reinforce the negative impact that dental pain causes on individuals' quality of life. 14,15,16 In certain circumstances, this high prevalence and intensity of dental pain are associated with gender, age, presence of carious cavities in the deciduous dentition, and number of dental visits. Corroborating the literature data, in the present study, the occurrence of pain related to a problem in the mouth was associated with age and the requirement for urgent care.…”
Section: Discussionmentioning
confidence: 99%